2019
DOI: 10.3389/fchem.2019.00531
|View full text |Cite
|
Sign up to set email alerts
|

A Mild, Fast, and Scalable Synthesis of Substituted α-Acyloxy Ketones via Multicomponent Reaction Using a Continuous Flow Approach

Abstract: A continuous flow approach for the synthesis of α-acyloxy ketone derivatives from the corresponding arylglyoxals, isocyanides, and carboxylic acids is described. The target products were obtained in excellent yields in short residence times and with high purities via the first transcription of the microwave-to-flow paradigm to the isocyanide-based Passerini reaction. Furthermore, this methodology allowed a 10-fold scale-up using the same experimental conditions initially established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“… 92 In 2019, the same group described another scalable procedure for the multicomponent isocyanide-based Passerini reaction optimized in the MW system ( Scheme 17 ). 93 From the optimization studies in batch mode, it was observed that in toluene and CHCl 3 , the conversion was very low or near-zero because of their low MW dielectric heating properties. In acetonitrile, the reaction efficiently delivered the desired product.…”
Section: Synthesis Of Heterocycles and Multicomponent Reactionmentioning
confidence: 99%
“… 92 In 2019, the same group described another scalable procedure for the multicomponent isocyanide-based Passerini reaction optimized in the MW system ( Scheme 17 ). 93 From the optimization studies in batch mode, it was observed that in toluene and CHCl 3 , the conversion was very low or near-zero because of their low MW dielectric heating properties. In acetonitrile, the reaction efficiently delivered the desired product.…”
Section: Synthesis Of Heterocycles and Multicomponent Reactionmentioning
confidence: 99%